Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/scs.0000000000003066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-Rich Fibrin on Peripheral Nerve Regeneration

Abstract: The study results suggest that PRF decreases functional recovery in sciatic nerve injury. Further studies are required to determine the efficacy of PRF on peripheral nerve regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…A total of 2 ml venous blood was drawn from the caudal vein of rats used in the experiment into a plain tube and immediately centrifuged at room temperature with a lab centrifuge (Electronic centrifuge 800, China) for 10 min at 3000 rpm 20 . In the middle of the tube, a fibrin clot was formed between the supernatant acellular plasma and the lower red corpuscles.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 2 ml venous blood was drawn from the caudal vein of rats used in the experiment into a plain tube and immediately centrifuged at room temperature with a lab centrifuge (Electronic centrifuge 800, China) for 10 min at 3000 rpm 20 . In the middle of the tube, a fibrin clot was formed between the supernatant acellular plasma and the lower red corpuscles.…”
Section: Methodsmentioning
confidence: 99%
“…Axon regeneration through conduits can be increased compared to that through empty collagen conduits by modifying their composition, architectures, and the factors/cells they contain. However, no conduit tested is as effective as allografts in inducing axon regeneration across both short and long gaps [55,68,204] under nerve injury conditions that are common clinically, such as a long gap in older patients that must be repaired at a long time post-trauma. An additional challenge is that the conduits that are most effective in animal models cannot be used clinically.…”
Section: Conclusion For Conduitsmentioning
confidence: 99%
“…68 In contrast, PRF failed to increase functional recovery in a 5-mm sciatic nerve gap as shown by functional, histopathologic and electrophysiologic analyses. 87 Although the PRF in these two studies was produced using the same protocol described by Choukroun et al , 23 the effective concentrations of activated platelets and released growth factors were not examined in the latter study, making it almost impossible to know whether the observed differences were due to inter-individual variation or the preparation method.…”
Section: Prp Treatment: Preparation and Biological Characteristicsmentioning
confidence: 99%